Research of structural organization of the personality of military service circular to alcohol abuse in the context of their gender-role status - Mozgovyi, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article deals with the features of the structural organization of the personality of the servicemen who are prone to alcohol abuse. Determined the further focus of the psychologist’s part with this category of persons, depending on the identified sex-role status of servicemen who are prone to alcohol abuse. According to the purpose the following tasks have been set: To investigate the specifics of the factor structure of servicemen who are prone to alcohol abuse; Identify the main pivotal features of their psychological portrait; To outline the main ways of psycho-corrective work with the personnel, who are prone to alcohol abuse depending on sexual role status. In total, 64 servicemen of the State Special Transport Service (MoDST) of the Ministry of Defense of Ukraine participated in the study. Research methods are: Prognosis, SZCh-4, HADS, CP-10, Kettel’s personal questionnaire, Shmishek’s test, self-esteem questionnaire, S. Bem method (determination of level of masculinity / femininity assessment) and structural gender-role scale (A. Kocharyan – EV Frolova), as well as Dur-Moll (masculinity-femininity, respectively) by S. Sondi’s method. The study revealed the character traits of a psychological portrait of servicemen who are prone to alcohol abuse: excitability, cyclothymia, anxiety, non-conformism and abusive behavior. The following key core personality indicators have been identified such as neuropsychiatric resistance, risk of nerve failure, and personal readiness to use inverted dynamics weapons. The focus of psycho-corrective influence of part of the psychologist on the personality of alcohol addicted servicemen should be to conduct training sessions aimed at forming a positive image of the serviceman.